IMPLEMENTASI ALGORITMA C 4.5 DAN ALGORITMA ID3 UNTUK MENGANALISIS KEPUASAN PELANGGAN TERHADAP PELAYANAN BENGKEL KENDARAAN BERMOTOR - Handika Syayuti Pratama (Jurnal Informatika: Jurnal Pengembangan IT, 2019)
AbstractThe growth of motor vehicle repair services business is a business that can be said to have a very high growth in Indonesia. This is due to the large number of motor vehicles in the country. Customer satisfaction in a business is important because of the satisfaction of the customer who will move the business forward. In this study results of consumer satisfaction survey in the workshop was analyzed using classification method with C 4.5 algorithm and Iterative Dichotomiser algorithm 3 (ID3). The results of the C 4.5 algorithm and the Iterative Dichotomiser algorithm 3 (ID3) Customers are satisfied with the reliability, Assurance (assurance) and responsiveness (responsiveness) attributes, while the less attributes are tangible (physical evidence). The C 4.5 algorithm and the Iterative Dichotomiser algorithm 3 (ID3) can be used to find the level of customer satisfaction with good value, enough, and less. From the calculation result two methods namely algorithm method C 4.5 and ID3 algorithm Get the result of the same decision tree, although the formula of two methods is different. While the suggested improvement of the results of this research is an improvement on the tangible attribute (physical evidence).Keywords : Workshop, C 4.5, Dichotomiser Iterative 3 (ID3), Classification.